Arab-Byzantine and Umayyad coins from Marea/Philoxenite: preliminary observations - Barbara Zając (Polish Archaeology in the Mediterranean)
Archaeological research at Marea/Philoxenite, conducted by the Polish Centre of Mediterranean Archaeology, University of Warsaw in collaboration with the Archaeological Museum in Kraków since 2000, has focused mainly on the site of the Great Basilica —one of the largest Christian basilicas of Egypt— and some other parts of the city. Research to date has shown that the city reached its peak development during the Byzantine period. It was one of the most important centers along the route leading from Alexandria to the sanctuary of Saint Menas at Abu Mina. To date, the site has yielded more than 8000 coins, the majority of them Late Roman minimi. Among the finds are a small group of Arab-Byzantine coins struck after the Arab conquest of Egypt in AD 640, as well as Umayyad coins introduced after the monetary reform of ʿAbd al-Malik ibn Marwān in AD 696/7. This article presents preliminary observations on the Arab-Byzantine and Umayyad coins discovered thus far in the course of fieldwork at Marea/Philoxenite.